Improving speaking fluency using video vision - Yuliana Ningsih; Adhiela Noer Syaief (Politeknik Negeri Bali, 2019)
This study aims to investigate the use of Video Vision on Machine Technology to improve students' English-speaking skills in Politeknik Negeri Tanah Laut. This research is action research conducted in two cycles with a subject of the 4th semester of the Mechanical Engineering Department in the Politeknik Negeri Tanah Laut in the course of ‘English for Communication’, academic year 2017/2018 with total 22 students. The data source is the result of an English-speaking skill test conducted at the end of each cycle. The data were analyzed quantitatively and quantitatively to determine the improvement of English-speaking skills in the learning process on the implementation of the Video Vision on Machine Technology in the classroom. The findings showed that there was an increase of learning process, from classical mastery in cycle 1 and the average absorption in Cycle 1, after continued cycle 2 and the result of classical mastery - average absorption also increased in the category ‘good’. Based on the results revealed that these learning media give a change in the learning process to improve students' English-speaking skills in the classroom by applying video vision on Machine Technology.